Genome Sequencing of Amomum tsao-ko Provides Novel Insight Into Its Volatile Component Biosynthesis - Sun, Fenghui; Yan, Chaochao; Lv, Yunyun; Pu, Zhonghui; Liao, Zedong; Guo, Wei; Dai, Min (Frontiers in Plant Science, 2022)
As an important economic and medicinal crop, Amomum tsao-ko is rich in volatile oils and widely used in food additives, essential oils, and traditional Chinese medicine. However, the lack of the genome remains a limiting factor for understanding its medicinal properties at the molecular level. Here, based on 288.72 Gb of PacBio long reads and 105.45 Gb of Illumina paired-end short reads, we assembled a draft genome for A. tsao-ko (2.70 Gb in size, contig N50 of 2.45 Mb). Approximately 90.07% of the predicted genes were annotated in public databases. Based on comparative genomic analysis, genes involved in secondary metabolite biosynthesis, flavonoid metabolism, and terpenoid biosynthesis showed significant expansion. Notably, the DXS, GGPPS, and CYP450 genes, which participate in rate-limiting steps for terpenoid backbone biosynthesis and modification, may form the genetic basis for essential oil formation in A. tsao-ko. The assembled A. tsao-ko draft genome provides a valuable genetic resource for understanding the unique features of this plant and for further evolutionary and agronomic studies of Zingiberaceae species.